MANAJEMEN DAKWAH HUMANIS PERSPEKTIF KH SHOLEH BAHRUDDIN: ANALISIS KONSEPTUAL DALAM KONTEKS MULTIKULTURAL: Konstruksi Konseptual dan Karakteristik Manajemen Dakwah Humanis,Implementasi Manajemen Dakwah Humanis dalam Masyarakat Multikultural,3. Relevansi dan Kontribusi Manajemen Dakwah Humanis dalam Merespons Intoleransi dan Menguatkan Dakwah Moderat, - Nela Cahya Anggraini; Ahmad Ega Nurul Ishaq; Abd Mukhit Karomi; Muhammad Rifky Maulana; Anang Sholikhudin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the concept of humanistic da’wah management from the perspective of KH Sholeh Bahruddin within a multicultural context. The background of this research is rooted in the increasing challenges of intolerance and exclusivism in religious preaching, which require a more inclusive and humane approach. This study aims to analyze the conceptual construction, characteristics, and relevance of humanistic da’wah management in addressing multicultural societal dynamics. This research employs a qualitative approach with a conceptual and library-based method, focusing on the analysis of primary and secondary sources related to the thoughts and practices of KH Sholeh Bahruddin. The results indicate that humanistic da’wah management emphasizes values such as tolerance, inclusivity, dialogue, and respect for diversity, distinguishing it from conventional, normative approaches. Furthermore, its implementation proves relevant in fostering social harmony and mitigating potential conflicts in multicultural societies. In conclusion, the humanistic da’wah management model contributes significantly to the development of a moderate, inclusive, and context-sensitive paradigm of Islamic preaching in contemporary settings.